ALGORITHM FOR THE SELECTION OF TREATMENT TACTICS FOR ACROMIAL END INJURIES OF THE CLAVICLE - Shukurov E.M; Djabbarov A.A. (Scholar Express Journals, 2024)
The authors have developed an algorithm and device for the treatment of damage to the acromial end of the clavicle. The developed algorithm for surgical treatment tactics and a device for treating damage to the acromial end of the clavicle has been introduced into practice. The results of treatment of 120 patients with fractures and fracture-dislocations of the acromial end of the clavicle, treated with various types of osteosynthesis, were studied. The results of surgical treatment of clavicle fractures were monitored for up to one year after removal of the device. Errors and complications in the applied options for surgical treatment of the clavicle are analyzed. Comparative assessments are given for each used variant of clavicle osteosynthesis. It was revealed that external osteosynthesis with the developed device against the background of the application of the developed algorithm for choosing a treatment method had the greatest positive results. (94.3%)
Keywords: damage to the acromial end of the clavicle; surgical treatment algorithm; evaluation of treatment results.